SAFETY AND IMMUNOLOGIC EFFICACY OF COMBINED IMMUNIZATION IN CHILDREN AGED 6—7 YEARS WITH VACCINES FROM THE NATIONAL CALENDAR OF PROPHYLACTICS VACCINES - I. V. Konovalov; O. V. Shamsheva; G. A. Elshina (Детские инфекции (Москва))
We estimated the safety of the vaccination for prevention of influenza with Grippol® plus vaccine alongside with vaccination with combined preparations for the prevention of diphtheria and tetanus (Td) and measles, rubella, mumps in children aged 6—7 years. We determined that combined immunization with the indicated vaccines proves good tolerability and low reactogenicity. Vaccine Grippol® Plus shows low reactogenicity , high immunologenicity and does not cause cross-suppression of antibodies in co-administration with other vaccines on vaccination calendar. Also concomitant vaccination with Grippol® plus and other vaccines does not inhibit the development of a specific immune response against influenza.